Innovation policy and the economy 4 - Jaffe, Adam B.; Lerner, Joshua; Stern, Scott (MIT Press, 2004)
The rapid pace of technological change brings with it an active debate about appropriate economic policies regarding research, innovation, and the commercialization of new technology. This annual series, sponsored by the National Bureau of Economic Research, provides a forum to bring the work of leading academic researchers to an audience of policymakers and those interested in the interaction between public policy and innovation.